2022
DOI: 10.1111/jne.13189
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic chemotherapy in patients with advanced neuroendocrine tumors: A single‐center retrospective analysis

Abstract: Neuroendocrine tumors (NETs) are more commonly slow-growing, therefore patients often receive chronic systemic therapies for tumor growth control and preservation of quality of life. Metronomic chemotherapy (mCT) is in line with this goal as it leads to stabilization of tumor growth over time without severe systemic toxicity. This is a retrospective analysis of patients with metastatic NETs receiving metronomic capecitabine (mCAP) or temozolomide (mTEM), at a NET-referral center. The aims of the study were to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Chan et al, for instance, reported on the effectiveness of a different therapeutic approach but did not provide a detailed breakdown by tumor grade or Ki-67 index, which is crucial for a nuanced understanding of treatment outcomes. Moreover, studies on the CAPTEM regimen, another recognized treatment for neuroendocrine tumors, present with a high degree of patient heterogeneity [16][17][18]20,[22][23][24]. This variability in patient profiles, encompassing a range of tumor grades and Ki-67 indices, adds complexity to any direct comparison with our results.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Chan et al, for instance, reported on the effectiveness of a different therapeutic approach but did not provide a detailed breakdown by tumor grade or Ki-67 index, which is crucial for a nuanced understanding of treatment outcomes. Moreover, studies on the CAPTEM regimen, another recognized treatment for neuroendocrine tumors, present with a high degree of patient heterogeneity [16][17][18]20,[22][23][24]. This variability in patient profiles, encompassing a range of tumor grades and Ki-67 indices, adds complexity to any direct comparison with our results.…”
Section: Discussionmentioning
confidence: 89%
“…Although the progression-free survival (PFS) exhibited by bevacizumab mirrored that of interferon, bevacizumab displayed a superior response rate, extended time to treatment failure (TTF), and a reduced incidence of side effects like fatigue [15]. Capturing the tumor cycle in low proliferating (slow-growing) neuroendocrine tumors is of paramount importance, and daily, low-dose continuous chemotherapy regimens might be aptly suited for this purpose [16][17][18]. Variations in dosing have been observed in studies focused on the metronomic application of TMZ [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations